The active role of courts in consumer litigation : applying EU law of the national courts' own motion / Anthi Beka. - Beka, Anthi (Intersentia, 2018)
The Active Role of Courts in Consumer Litigation traces the emergence of a specific EU Law doctrine governing the role of the national courts in proceedings involving consumers that whilst only established more recently, has already become an important benchmark for effective consumer protection. According to the 'active consumer court' doctrine, developed in the case-law of the CJEU, national courts are required to raise, of their own motion, mandatory rules of EU consumer contract law, notably those protecting consumers from the use of unfair terms. This results in the strengthening of procedural consumer protection standards in ordinary proceedings but also in payment order proceedings, consumer insolvency proceedings or repossession proceedings directed against the primary family residence of the mortgage debtor. The considerations of contractual imbalance will now have to be taken into account in court proceedings leading, where necessary, to the reform of national procedural safeguards to protect the weaker contractual party. Dr Anthi Beka is a legal administrator with the chambers of Judge M. Vilaras in the Court of Justice of the European Union. She holds a PhD from the Faculty of Law, University of Luxembourg.